Viral glycoproteins destined for apical or basolateral plasma membrane domains traverse the same Golgi apparatus during their intracellular transport in doubly infected Madin-Darby canine kidney cells (The Rockefeller University Press, 1984)
Madin-Darby canine kidney (MDCK) cells can sustain double infection with pairs of viruses of opposite budding polarity (simian virus 5 [SV5] and vesicular stomatitis virus [VSV] or influenza and VSV), and we observed that in such cells the envelope glycoproteins of the two viruses are synthesized simultaneously and assembled into virions at their characteristic sites. Influenza and SV5 budded exclusively from the apical plasma membrane of the cells, while VSV emerged only from the basolateral surfaces. Immunoelectron microscopic examination of doubly infected MDCK cells showed that the influenza hemagglutinin (HA) and the VSV G glycoproteins traverse the same Golgi apparatus and even the same Golgi cisternae. This indicates that the pathways of the two proteins towards the plasma membrane do not diverge before passage through the Golgi apparatus and therefore that critical sorting steps must take place during or after passage of the glycoproteins through this organelle. After its passage through the Golgi, the HA accumulated primarily at the apical membrane, where influenza virion assembly occurred. A small fraction of HA did, however, appear on the lateral surface and was incorporated into the envelope of budding VSV virions. Although predominantly found on the basolateral surface, significant amounts of G protein were observed on the apical plasma membrane well before disruption of the tight junctions was detectable. Nevertheless, assembly of VSV virions was restricted to the basolateral domain and in doubly infected cells the G protein was only infrequently incorporated into the envelope of budding influenza virions. These observations indicate that the site of VSV budding is not determined exclusively by the presence of G polypeptides. Therefore, it is likely that, at least for VSV, other cellular or viral components are responsible for the selection of the appropriate budding domain.